The Impact of Strategic Human Resources Planning on Localizing Jobs in Saudi Arabia: Analytical inductive study (International Journal of Financial, Administrative and Economic Sciences, 2025)
The research "The Impact of Strategic Human Resources Planning on Localizing Jobs in Saudi Arabia" consists of an analytical study; it consists of three main chapters, each chapter was divided into three topics, and each topic contained a number of sub-headings.In the first chapter, the researcher talked about strategic planning for human resources; the first topic talked about the general concepts of strategic planning and covered several titles, including the concept of planning and the concept of strategy, then the definition of strategy and the definition of strategic management, then the definition of strategic planning, then concluded by presenting the difference between strategic management and strategic planning. As for the second topic, strategic planning for human resources, the researcher began talking about the historical development of human resources management, then discussed the concept of human resources management and then the definitions of human resources management, as well as the definitions of strategic management for human resources with their differences. It was necessary when talking about strategy to define human resources planning, its objectives and importance, then clarify the relationship between human resources planning and strategic planning, and finally the most important requirements for managers of strategic human resources management were presented. As for the third topic, it dealt with the basic requirements for implementing strategic management for human resources.The second chapter discusses job localization as a process of qualitative and quantitative replacement of foreign labor by national labor. In the first section, he discusses the concept of job localization and its objectives. In the second section, he discusses the different methods and approaches of job localization. In the third section, he discusses a group of challenges and obstacles facing the process of job localization, social, political, economical, and other obstacles.Chapter Three: Job Saudization as a local concept for job localization in the Kingdom of Saudi Arabia. The first section discussed the concept and definition of job Saudization. Then, in the second section, the researcher presented a realistic picture of job Saudization between reality and hope, which led to the reality embodied in the vision of the Kingdom of Saudi Arabia 2023. Finally, like other plans, Saudization is not without some problems and obstacles. This was mentioned in the third section entitled Obstacles and problems in implementing job Saudization.In the conclusion of the research, the researcher discussed a number of results that he reached through inductive analysis, text analysis, comparisons and analyses that he conducted to arrive at some recommendations that the researcher sees as important for the authorities responsible for the matter of localizing jobs and the authorities implementing them. Finally, the researcher monitored the sources and references that he used in his research.
Keywords: Strategic Human Resources Planning; Localization of Jobs in Saudi Arabia